LITTER DECOMPOSITION IN SOILS OF OVERGROWN GRASSLANDS IN DEPENDANCE OF TEMPERATURE - Marjetka SUHADOLC; Zalika ČREPINŠEK (Acta Agriculturae Slovenica)
The aim of the study was to examine whether the effect of projected temperature rises due to the global climate change could accelerate plant litter decomposition in soils of overgrown grasslands. The experiment was carried out under natural conditions at the locations of Bohinj-Polje and Uskovnica with similar environmental conditions (precipitation, parent material and soil development, plant communities) and the difference in air temperatures. The average difference in monthly air temperatures during our study were higher in Bohinj for 4.4 °C (± 1.5 °C) than in Uskovnica. Nylon mesh bags with mixed plant litter from both locations were placed into the Of horizon of the soil profiles at both locations in autumn 2007. The litter bags were sampled successively at 4 sampling times until May 2009 in 5 replicates. The litter degradation, expressed as mass loss, was throughout our study 57.1 ± 1.2 % (0 - 526 days) in Bohinj, 57.3 ± 2.6 % (0 - 555 days) at Uskovnica. No statistically significant differences in litter decomposition rate and seasonal pattern of mass loss was found between the sites. The dynamics of the total content of cellulose and lignin, Corg and N and their soluble forms (DOC and DON) were similar between the sites as well. The lignin content in the plant material did not statistically significantly change during the experiment. The results of our experiment did not confirm the effect of the difference in average air temperature on decomposition rate decreases. The results did not confirm any effect from the difference in the average monthly air temperature between the sites on the plant litter decomposition in our study.